Patterns of compensatory mutations in rpoA/B/C genes of multidrug resistant M. tuberculosis in Uganda - David Patrick Kateete; Shakira Namakula; Edgar Kigozi; Fred A. Katabazi; George William Kasule; Kenneth Musisi; Edward Wampande; Deus Lukoye; Moses L. Joloba (PLoS ONE, 2025)
Mutations in rpoB , a gene that encodes the bacterial RNA polymerase (RNAP) beta-subunit, can cause high-level resistance to rifampicin. Approximately 95% of rifampicin-resistant Mycobacterium tuberculosis clinical isolates harbour mutations in an 81-base pair rpoB region referred to as the rifampicin-resistance-determining region ( rpoB /RRDR). Also, rifampicin-resistant M. tuberculosis clinical isolates carry multiple mutations in RNAP genes (i.e., rpoA, rpoB , rpoC, rpoD ), particularly rpoA and rpoC, which encode the alpha- (α 2 ) and beta′- (β′) subunits, respectively. Such secondary mutations offset the fitness cost associated with acquisition of rifampicin-resistance mutations in M. tuberculosis , resulting in resistant strains that are as fit as the wild-type drug-susceptible strains. To analyse the patterns of compensatory mutations in RNAP encoding genes of rifampicin-resistant M. tuberculosis clinical isolates in Uganda, whole genome sequencing and Sanger DNA sequencing were performed on 52 M. tuberculosis clinical isolates – 20 drug-susceptible and 32 multidrug resistant (MDR). A total of 24 (75%) MDR-TB isolates had high-level rifampicin-resistance-conferring mutations in rpoB /RRDR, i.e., Ser531Leu (31%); His526Asp (6%); His526Leu (3%); His526Tyr (3%); His526Arg (3%); His526Gly (3%); Asp516Tyr (13%); Asp516Val (6%); Glu513Lys (3%); Leu511Pro (3%); Leu492Leu (3%); Gln490Arg (3%). Further, two putative compensatory mutations (Gln490Arg & Lys1025Glu) outside the RRDR and not resistance-conferring were found in rpoB . Altogether, 15 (63%, 15/24) MDR-TB isolates with rpoB /RRDR resistance-conferring mutations had non-synonymous mutations in rpoC of the following patterns Leu39Phe (3%); Tyr61His (3%); Asp271Gly (3%); Ser377Ala (3%); Pro481Thr (3%); Val483Ala (6%); Leu516Pro (3%); Ala521Asp (3%); Gly594Glu (13%); Asn698Ser (3%); Leu823Pro (3%). In conclusion, putative compensatory mutations are prevalent in rifampicin-resistant M. tuberculosis clinical isolates in Uganda, with rpoC /Gly594Glu and rpoC /Val483Ala as the most frequent. Further studies will determine their association with strain genetic background, fitness and transmission in an endemic setting with a high burden of HIV-TB coinfection.